Investigating myocardial energetic deficit across the spectrum of cardiac disease. (3rd October 2022) - Henry, J A; Levelt, E; Rayner, J J; Hundertmark, M J; Peterzan, M A; Green, P G; Watson, W; Burrage, M K; Arvidsson, P; Lewis, A J M; Chamley, R; Neubauer, S; et al.
Abstract: Introduction: The phosphocreatine-to-adenosine triphosphate ratio (PCr/ATP) is a sensitive marker of the energetic state of the heart and can be reliably measured non-invasively using 31Phosphorus magnetic resonance spectroscopy (31P-MRS). Derangements in cardiac energetics are a distinctive feature in the pathophysiology of several cardiac diseases, and thus potential therapeutic targets. Purpose: We sought to compare cardiac PCr/ATP across a range of cardiac pathologies. Methods: Using a 3D chemical shift 31P spectral acquisition we recorded PCr/ATP in 515 participants: athletes (n=17), healthy controls with normal weight (n=148), overweight (n=67) and with obesity (n=73), diabetes (n=23), heart failure with preserved ejection fraction (HFpEF) (n=33), heart failure with reduced ejection fraction (HFrEF) (n=63), amyloid (n=9), severe aortic stenosis (AS) (n=29), severe mitral regurgitation (MR) (n=18), and hypertrophic cardiomyopathy (HCM) (n=35). Results: A spectrum of myocardial PCr/ATP exists ranging from normal in athletes (2.23±0.28) and those with normal weight (2.05±0.38) to severely impaired in severe MR (1.56±0.32) and cardiac amyloid (1.34±0.19, Figure 1). Despite normal systolic function (all LVEF >57%) those living with obesity and diabetes have lower PCr/ATP than normal (all p<0.001). In all groups with HF, regardless of aetiology, myocardial energetics were impaired (all p<0.001). Across the whole cohort PCr/ATP was negatively correlated with body mass index (r −0.28, p<0.001), age (r −0.34, p<0.001) and LV mass (r −0.1, p<0.001). PCr/ATP was not related to systolic or diastolic blood pressure in these cohorts. Conclusions: We demonstrate a spectrum of energetic deficit in cardiac disease and this is affected by not only myocardial pathology but also by obesity and age. Derangements in myocardial energetics are present in myocardial pathologies independent of underlying aetiology. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): We acknowledge support from the British Heart Foundation Oxford Center of Research Excellence.